SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PELAKU USAHA TERBAIK BERBASIS WEB - Mulyadi, Erwin; Manik, Ngarap Immanuel; Moniaga, Jurike V. (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Following the COVID-19 PPKM in place, businesses need new strategies to re-market their products so that they can continue to transact with other businesses and MSMEs. To address this, a study was conducted using mathematical and computer models. This study aimed to design a decision support system to determine the best business from five business sectors: Food, Clothing, Automotive, Services, and Electronics. The Multi-Attribute Utility Theory method was used to determine the best business, implemented web-based. Based on blackbox testing, the application performed well, from displaying pages, saving data, deleting data, and modifying data. Furthermore, user satisfaction evaluation, based on the results of a survey of five measurable human factors, demonstrated ease of use, with users providing positive feedback.